Effect of SQ3R on Students’ Reading Comprehension - Cataraja, Geryl (Future Science / FSH-PH Publications, 2022)
Comprehension is the primary objective reading, which promotes cognizance in all disciplines and so improves the teaching-learning process. The objective of this research was to see how SQ3R affected the reading comprehension of Grade 11 students at the Palompon Institute of Technology. The pretest-posttest control group design was employed in this research. Sixty Students randomly assigned to either of the groups. To gather the data, a reading comprehension test was used. It was treated using the mean and t-tests for dependent and independent samples. The following findings were revealed: 1) The initial reading comprehension of the SQ3R was “fair to good” while the conventional reading strategy was also “fair to good.” 2) The students’ initial reading comprehension was of the same level; 3)The final reading comprehension of the SQ3R was better than the conventional reading strategy ; 4) A significant difference was found between the initial and final reading comprehension of the students exposed to the SQ3R as well as those to the conventional reading strategy; and 5) There was a significant difference between the reading comprehension of the students exposed to the SQ3R and to the conventional reading strategy. This means that the SQ3R is a more effective strategy than conventional reading in the development of the students’ reading comprehension. On the above findings, it was concluded that students need a different reading strategy to improve their reading comprehension, but they perform better if they use the SQ3R instead of conventional reading strategy.